CHITOSAN SEBAGAI BAHAN KOAGULAN LIMBAH CAIR INDUSTRI TEKSTIL - Prayudi, Teguh; Susanto, Joko Prayitno (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
The industrial development for textile in Indonesia has created environmental problem caused by its untreated wastes due to limited inexpensive waste treatment technology available. Chitosan is a chemical compound that can be obtained easily from chitin made from crabs and shrimps shell with is abundantly available in Indonesia. One of its superiority characteristic of chitosan is its capability in bonding colloidal solution and heavy metals in textile waste. The aim of this research studies is assessing the capability of chitosan to bond the colloidal solution in industrial waste treatment process especially for textile industry.